The magnetic field effect on electron beam generation in magnetron injection guns with secondary-emission cathodes - Dovbnya, A.N.; Zakutin, V.V.; Reshetnyak, N.G.; Romas’ko, V.P.; Bovda, A.M.; Utva, O.M.; Pokas, V.F.; Jeran, L.V.; Krasnogolovets, M.A.; Volkolupov, Yu.Ya. (Вопросы атомной науки и техники, 1999)
Magnetron guns with secondary-emission cathodes appear promising for the use as electron sources in high-power microwave devices [1, 2]. For stable beam generation, the magnetic field in the gun is calculated to be between 0.5 to 5 kG, depending on the cathode voltage amplitude and the gun dimensions. On the other hand, the beam transport in the resonance system of the microwave device also calls for rather high magnetic fields. The generation of these fields of significant extent to produce and transport the beam is a rather grave problem. It is generally solved by using water-cooled solenoids [3], that gives rise to considerable difficulties. In recent years, constant magnets have been used [3] to generate extended solenoidal magnetic fields. So, it was of interest to investigate both the generation of such fields and their effect on beam production and parameters in the magnetron gun.